THE EFFECT OF CAPITAL STRUCTURE AND SALES GROWTH ON FINANCIAL DISTRESS WITH PROFITABILITY AS A MODERATING VARIABLE: EVIDENCE FROM INDONESIA MANUFACTURING FIRMS - Noor, Kania Syahra; Tjong, William (Universitas Pelita Harapan, 2025)
This study examines the impact of capital structure and sales growth on financial distress, with profitability as a moderating variable. Using 326 firm-year observations from 84 Indonesian manufacturing companies in the consumer discretionary and consumer staples sectors (2019–2023), logistic regression and moderated regression analysis were applied. The findings show that the debt-to-equity ratio and sales growth significantly increase the likelihood of financial distress, while profitability reduces it. In contrast, the debt-to-asset ratio has no significant effect, and profitability does not moderate the effects of capital structure or sales growth. These results provide evidence for the inconsistent findings in prior studies and highlight the need for managers to balance leverage, growth, and profitability to reduce financial risk. Keywords: Capital Structure; Sales Growth; Profitability; Financial Distress; Altman Z- Score; Indonesia